The Effect of Working Capital on the Profitability of Pharmaceutical Companies Listed in the Indonesia Sharia Stock Index (ISSI) - Meilvinasvita, Dwi; Arifai, Muhammad; Zulkarnaini, Zulkarnaini; Diana, Diana (Politeknik Negeri Bengkalis, 2024)
The purpose of this paper is to examine the factors affecting profitability of pharmaceutical company inIndonesia. This research is based on three independent variables that were empirically examined for working capitalrelationship with profitability. These variables are Cash Turn Over, Receivable Turn Over, Inventory Turn Over. Data offive pharmaceutical companies listed on in the Indonesia Sharia Stock Index covering the period of 2018–2023 wereextracted from companies’ annual reports. The findings of this research show that cash turnover, accounts receivableturnover and inventory turnover simultaneously influence profitability. Partially, cah turnover does not have a significanteffect on profitability. Meanwhile, receivables turnover and inventory turnover have a significant effect on profitability,with a coefficient of determination (R2) of 72,8%. The results provide a basis for future research in this field and caninform decision-making for pharmaceutical firms looking to improve their financial performance.pharmaceutical firmslooking to improve their financial performance.